Expression analysis of aldehyde dehydrogenase 1A1 (ALDH1A1) in colon and rectal cancer in association with prognosis and response to chemotherapy - Kahlert, Christoph; Gaitzsch, Eva; Steinert, Gunnar; Mogler, Carolin; Herpel, Esther; Hoffmeister, Michael; Jansen, Lina; Benner, Axel; Brenner, Hermann; Chang-Claude, Jenny; Rahbari, Nuh Nabi; Schmidt, Thomas; et al. (Annals of surgical oncology, 2012)
Background: Aldehyde dehydrogenase 1A1 (ALDH1A1) has been described as a cancer stem cell marker and as a regulator of cellular chemoresistance. Therefore, ALDH1A1 has been suggested as potential biomarker to stratify patients into different risk categories for a “personalized” therapy approach. We have investigated the prognostic role of ALDH1A1 in primary colorectal cancer and its value in predicting response to chemotherapy in metastatic colorectal cancer. Methods: Immunostaining against ALDH1A1 was performed on a paraffin-embedded tissue microarray including 659 primary colon cancer samples and 338 rectal cancer samples. Likewise, tissue of 44 palliatively resected colorectal liver metastases on whole-mount tissue slides was immunostained against ALDH1A1. Cytoplasmic, nuclear, and stromal expression of ALDH1A1 was assessed and merged with histopathological and clinical data. Results: Univariate and multivariate analysis revealed that cytoplasmic and stromal expression of ALDH1A1 is not significantly associated with prognosis either in colon or in rectal cancer. Furthermore, cytoplasmic expression of ALDH1A1 does not predict response to palliative chemotherapy in patients with metastatic diseases. Intriguingly, as a novel finding, nuclear expression of ALDH1A1 was observed in a small subgroup of patients with colon cancer and rectal cancer. In colon cancer, nuclear expression was significantly associated with shortened overall survival by univariate and multivariate analysis. Conclusions: Immunohistochemical expression analysis of ALDH1A1 in colon cancer is useful for the detection of nuclear expression in a small subpopulation of patients and is associated with shorter survival. Cytoplasmic expression fails to be of clinical relevance as prognostic or predictive marker in colorectal cancer.